2021
DOI: 10.1515/tnsci-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lncRNA H19/miR-370-3p pathway mitigates neuronal apoptosis in an in vitro model of spinal cord injury (SCI)

Abstract: Background Spinal cord injury (SCI) is the most serious complication of spinal injury, often leading to severe dysfunction of the limbs below the injured segment. Conventional therapy approaches are becoming less and less effective, and gene therapy is a new research direction by now. Methods The Sprague-Dawley rats were haphazardly assigned to two groups, namely sham group and SCI model group, and lncRNA H19 and miR-370-3p l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The causes of cell apoptosis are complex, and it is often a process involving multiple injury factors and multiple apoptosis-related genes simultaneously or successively [ 32 ]. The induced pro-inflammatory cytokines [ 33 ] also lead to nerve cell apoptosis, which is the main reason for the loss of motor function and difficulty in recovery after SCI [ 6 , 34 ]. BRB-AuNCs reduced the production of IL-1β, IL-6 and TNF-α, indicating their anti-inflammatory effects, thereby the apoptosis was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…The causes of cell apoptosis are complex, and it is often a process involving multiple injury factors and multiple apoptosis-related genes simultaneously or successively [ 32 ]. The induced pro-inflammatory cytokines [ 33 ] also lead to nerve cell apoptosis, which is the main reason for the loss of motor function and difficulty in recovery after SCI [ 6 , 34 ]. BRB-AuNCs reduced the production of IL-1β, IL-6 and TNF-α, indicating their anti-inflammatory effects, thereby the apoptosis was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al showed that the expression of LncRNA H19 was significantly up-regulated after spinal cord injury in rats [ 29 ]. Silencing LncRNA H19 can effectively alleviate lipopolysaccharide (LPS)-induced cell injury, but also reduce the expression of caspase-3, Bax and other proteins and neuronal apoptosis rate [ 29 ].…”
Section: Role Of Lncrnas In the Pathological Process Of Spinal Cord I...mentioning
confidence: 99%
“…Li et al showed that the expression of LncRNA H19 was significantly up-regulated after spinal cord injury in rats [ 29 ]. Silencing LncRNA H19 can effectively alleviate lipopolysaccharide (LPS)-induced cell injury, but also reduce the expression of caspase-3, Bax and other proteins and neuronal apoptosis rate [ 29 ]. In the treatment experiment of spinal cord injury rats, down-regulation of LncRNA H19 can inhibit neuronal apoptosis through enhancer of zeste homolog 2 (EZH2)/Notch axis [ 30 ].…”
Section: Role Of Lncrnas In the Pathological Process Of Spinal Cord I...mentioning
confidence: 99%
“…LncRNA H19 is correlated with neurological disorders such as intracranial aneurysms, ischemic stroke, glioma, and neuroblastoma [ 12 ]. Recent studies indicate that abnormal lncRNA H19 expression affected neurons apoptosis and inflammation after SCI [ 13 ], and lncRNA H19 was reported to regulate microglia pyroptosis [ 14 , 15 ]. However, the exact role of H19 in neuron pyroptosis during SCI/R is still not well understood.…”
Section: Introductionmentioning
confidence: 99%